Strategi Pencegahan dan Pengurangan Keterlambatan Mahasiswa Dalam Menyelesaikan Studi - Angel Angreni Malau; Deya Yuna Rusydiana Abrara; Juni Arta Sinaga; Romaulina Simarmata; Christina Natalia Simarmata; Luciana Chris May Purba; Imelia Sapitri Purba; Yesina Lubis; Novita Tiambun Sinaga; Rima Melati; Angeleva Revi Christa Sinaga (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This journal article presents a research study that aims to provide a comprehensive understanding of the phenomenon under investigation through a mixed-methods research approach. The study utilizes a combination of quantitative and qualitative methods to collect and analyze data. The data collection is conducted using Google Form, which includes both closed-ended questions for quantitative data and open-ended questions for qualitative data. The collected data is then analyzed using statistical analysis for quantitative data and thematic analysis for qualitative data. The research findings contribute to the advancement of knowledge by offering a holistic perspective on the researched topic. The study sheds light on the factors contributing to student delays in completing their studies and explores strategies for prevention and reduction. The results highlight the importance of intensive academic guidance programs, optimal scheduling, strong academic support, active student engagement, mentoring, peer tutoring, and effective monitoring systems in addressing student delays. These findings have implications for educational policies, practices, and social actions aimed at improving student success and timely completion of studies.